Delphinidin inhibits BDNF-induced migration and invasion in SKOV3 ovarian cancer cells. Issue 23 (1st December 2017) - Lim, Won-Chul; Kim, Hyunhee; Kim, Young-Joo; Park, Seung-Ho; Song, Ji-Hye; Lee, Ki Heon; Lee, In Ho; Lee, Yoo-Kyung; So, Kyeong A.; Choi, Kyung-Chul; Ko, Hyeonseok
Graphical abstract: Abstract: Brain-derived neurotrophic factor (BDNF), the TrkB ligand, is associated with aggressive malignant behavior, including migration and invasion, in tumor cells and a poor prognosis in patients with various types of cancer. Delphinidin is a diphenylpropane-based polyphenolic ring structure-harboring compound, which exhibits a wide range of pharmacological activities, anti-tumor, anti-oxidant, anti-inflammatory, anti-angiogenic and anti-mutagenic activity. However, the possible role of delphinidin in the cancer migration and invasion is unclear. We investigated the suppressive effect of delphinidin on the cancer migration and invasion. Thus, we found that BDNF enhanced cancer migration and invasion in SKOV3 ovarian cancer cell. To exam the inhibitory role of delphinidin in SKOV3 ovarian cancer migration and invasion, we investigated the use of delphinidin as inhibitors of BDNF-induced motility and invasiveness in SKOV3 ovarian cancer cells in vitro . Here, we found that delphinidin prominently inhibited the BDNF-induced increase in cell migration and invasion of SKOV3 ovarian cancer cells. Furthermore, delphinidin remarkably inhibited BDNF-stimulated expression of MMP-2 and MMP-9. Also, delphinidin antagonized the phosphorylation of Akt and nuclear translocation of NF-κB permitted by the BDNF in SKOV3 ovarian cancer cells. Taken together, our findings provide new evidence that delphinidin suppressed the BDNF-induced ovarian cancer migration and invasion through decreasing of Akt activation.